2015
DOI: 10.1186/s12967-015-0668-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum proteome signatures of locally advanced and metastatic gastric cancer: a pilot study

Abstract: BackgroundThe gastric cancer is one of the most common and mortal cancer worldwide. The initial asymptomatic development and further nonspecific symptoms result in diagnosis at the advanced stage with poor prognosis. Yet, no clinically useful biomarkers are available for this malignancy, and invasive gastrointestinal endoscopy remains the only reliable option at the moment. Hence, there is a need for discovery of clinically useful noninvasive diagnostic and/or prognostic tool as an alternative (or complement) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The GC patients globally showed higher levels of FpA compared with healthy controls, so FpA was proposed as a potential marker for GC detection (Table ). Serum peptidome analyses by either matrix‐assisted laser‐desorption ionization or surface‐enhanced laser‐desorption ionization time‐of‐flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC . Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages …”
Section: Coagulation‐related Proteins and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The GC patients globally showed higher levels of FpA compared with healthy controls, so FpA was proposed as a potential marker for GC detection (Table ). Serum peptidome analyses by either matrix‐assisted laser‐desorption ionization or surface‐enhanced laser‐desorption ionization time‐of‐flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC . Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages …”
Section: Coagulation‐related Proteins and Cancermentioning
confidence: 99%
“…Serum peptidome analyses by either matrix-assisted laser-desorption ionization or surface-enhanced laser-desorption ionization time-of-flight mass spectrometry revealed FpA peptide as a m/z peak at around 1469 Da particularly upregulated in metastatic GC or in GC with lymph node metastasis, as well as in patients at high risk for GC. [120][121][122][123] Previous laboratory assays showed that FpA levels increased with the extent of primary tumor in postoperative patients with malignant disease since its early stages. [124][125][126][127] Fibrinolysis: DD as an indicator of thrombosis, cancer progression, and response to therapy As a compensation mechanism for fibrin clot formation, fibrinolysis is activated, which consists of fibrin degradation by the sequential action of three enzymes: thrombin, factor XIIIa, and plasmin.…”
mentioning
confidence: 99%
“…The use of MALDI-TOF-MS profiling enables to obtain a whole pattern of low-molecular weight proteins occurring in human serum and was indicated as a promising strategy in several cancer research. This technology was found to be effective in discrimination of healthy individuals from patients with various tumors such as biliary tract cancer [ 32 ], gastric cancer [ 33 ], prostate cancer [ 34 ], ovarian cancer [ 16 ] and head and neck cancer [ 35 ]. Moreover, serum peptidome features were suggested to be useful in monitoring the toxicity of applied therapy in women with breast cancer [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics complements the genomic and transcriptomics approaches, providing additional information about the protein expression and post-translational modifications. Most of proteomics studies in this field so far focused on the discovery of gastric cancer associated biomarkers from plasma samples (Uen et al, 2013;Abramowicz et al, 2015;Gao et al, 2015;Yoo et al, 2017). An early study (Uen et al, 2013) investigated the glycoprotein profiles of serum samples from gastric cancer patients and healthy subjects.…”
Section: Proteomics and Metabolomics In Gastric Cancermentioning
confidence: 99%